Calcified Aortic Valve Disease in Patients With Familial Hypercholesterolemia. Issue 5 (November 2020) - Hu, Haochang; Cheng, Ji; Lin, Shaoyi; Wang, Shuangshuang; Chen, Xiaomin
Abstract : Abstract: Familial hypercholesterolemia (FH) is a rare autosomal gene deficiency disease with increased low-density lipoprotein cholesterol, xanthoma, and premature coronary heart disease. Calcified aortic valve disease (CAVD) is prevalent in FH patients, resulting in adverse events and heavy health care burden. Aortic valve calcification is currently considered an active biological process, which shares several common risk factors with atherosclerosis, including aging, hypertension, dyslipidemia, and so on. Unfortunately, the pathogenesis and therapy of CAVD in FH are still controversial. There is no pharmacological intervention recommended to delay the development of CAVD in FH, and the only effective treatment for severe CAVD is aortic valve replacement. In this review, we summarize the detailed description of the pathophysiology, molecular mechanism, risk factors, and treatment of CAVD in FH patients.